No neuroprotective effect of therapeutic hypothermia following lipopolysaccharide-sensitized hypoxia-ischemia: a newborn piglet study - Mads Andersen; Mads Andersen; Hannah Brogård Andersen; Hannah Brogård Andersen; Ted Carl Kejlberg Andelius; Ted Carl Kejlberg Andelius; Lærke Hjøllund Hansen; Lærke Hjøllund Hansen; Regitze Pinnerup; Regitze Pinnerup; Mette Bjerre; Steffen Ringgaard; et al. (Frontiers Media S.A., 2023)
IntroductionTherapeutic hypothermia is the only proven neuroprotective treatment for hypoxic-ischemic encephalopathy. However, studies have questioned whether therapeutic hypothermia may benefit newborns subjected to infection or inflammation before a hypoxic-ischemic insult. We aimed to compare newborn piglets with lipopolysaccharide-sensitized hypoxia-ischemia treated with and without therapeutic hypothermia with regards to measures of neuroprotection.MethodsA total of 32 male and female piglets were included in this randomized experimental study. Lipopolysaccharides from Escherichia coli were infused intravenously before initiation of a standardized global hypoxic-ischemic insult. The piglets were then randomized to either normothermia or therapeutic hypothermia. After 14 h, the piglets were evaluated. Our primary outcome was brain lactate/N-acetylaspartate ratio assessed by magnetic resonance spectroscopy. Secondary outcomes included measures of magnetic resonance imaging, amplitude-integrated electroencephalography, immunohistochemistry, and concentration of blood cells and cytokines.ResultsPiglets treated with and without therapeutic hypothermia were subjected to comparable global hypoxic-ischemic insults. We found no difference between the two groups with regards to measures of magnetic resonance spectroscopy and imaging, amplitude-integrated electroencephalography, immunohistochemistry, and concentration of blood cells and cytokines.ConclusionWe found no indication of neuroprotection by therapeutic hypothermia in newborn piglets following lipopolysaccharide-sensitized hypoxia-ischemia. However, interpretation of the results is limited by the short observation period. Further studies are required to determine the potential clinical implications of these findings.